Penerapan Model Pembelajaran Kooperatif Tipe NHT dengan Berbatuan LKPD Untuk Meningkatkan Hasil Belajar Siswa Kelas X SMA Negeri 1 Stabat - Vania Dwisaura Artanti; Mukhtar Mukhtar (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2024)
This study aims to determine whether the NHT type cooperative learning model with the help of LKPD can improve student learning outcomes in grade X of SMA Negeri 1 Stabat. This type of research is Classroom Action Research (PTK) or action research which consists of 2 cycles, where each cycle consists of 1 meeting. The subjects in this study were students of grade X Science 1 SMA Negeri 1 Stabat consisting of 36 students. The object of this study is the results of student learning with the application of the Numbered Head Together type cooperative learning model with the help of Student Worksheets in grade X Science 1 SMA Negeri 1 Stabat. From the results of the study can be concluded the following: (1) There is an increase in students' mathematics learning outcomes. This can be seen by the achievement of classical completeness in the initial test obtained 30.56%, in the learning outcome test I increased to 61.11%, and in the learning outcome test II increased to 86.11%, so that based on the results of the data analysis it was obtained that this study had reached the specified success indicators. (2) After the implementation of the Numbered Head Together learning model with the help of Student Worksheets, students' mathematics learning outcomes have been classically completed to 86.11%.